2011
DOI: 10.1590/s1516-89132011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity in soil cultivated with different summer legumes in coffee crop

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
2
10
0
2
Order By: Relevance
“…The soil chemical properties after 10 years under different legume green manures (Table 1) are discussed by Balota & Chaves (2010). The average values of enzyme activity, total C and C and N mineralization of eight samplings in two years indicated that intercropping of different summer legume species as green manure influenced microbial activity, both under the coffee canopy and in-between rows.…”
Section: Resultsmentioning
confidence: 99%
“…The soil chemical properties after 10 years under different legume green manures (Table 1) are discussed by Balota & Chaves (2010). The average values of enzyme activity, total C and C and N mineralization of eight samplings in two years indicated that intercropping of different summer legume species as green manure influenced microbial activity, both under the coffee canopy and in-between rows.…”
Section: Resultsmentioning
confidence: 99%
“…A high correlation between microbial biomass and organic C was previously observed by Balota et al (2003), Araújo et al (2008) and Balota & Chaves (2011). The significant relationship between microbial biomass and organic C is likely due to the fact that higher organic matter levels support greater microbial biomass and activity.…”
Section: Resultsmentioning
confidence: 53%
“…The values obtained in this study are similar to those observed under different soil conditions and management systems in other regions of Paraná State (using the same analytical methods) (Balota et., 2004;Balota & Chaves, 2011). The wide range for this relationship due to soil management may suggest its high sensibility to express C turnover pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Results from Crusciol et al (2013) and Balota;Chaves (2011) show that the C/N ratio of Mucuna pruriens (16.4) is lower than that from Cajanus cajan (32). However, the chemical composition of these leguminous crops is similar, particularly in the aromatic carbon compound region, confirming the relationship between the composition of carbon compounds and the decomposition of plant material (RANDAL et al, 1997).…”
Section: Resultsmentioning
confidence: 98%